Estimating Private Equity Returns from Limited Partner Cash Flows - ANG, ANDREW; CHEN, BINGXU; GOETZMANN, WILLIAM N.; PHALIPPOU, LUDOVIC (Journal of Finance, 2018)
ABSTRACT We introduce a methodology to estimate the historical time series of returns to investment in private equity funds. The approach requires only an unbalanced panel of cash contributions and distributions accruing to limited partners and is robust to sparse data. We decompose private equity returns from 1994 to 2015 into a component due to traded factors and a time‐varying private equity premium not spanned by publicly traded factors. We find cyclicality in private equity returns that differs according to fund type and is consistent with the conjecture that capital market segmentation contributes to private equity returns.